Pengaruh Stabilitas Keuangan, Tekanan Eksternal, Pergantian Auditor terhadap Kecurangan Laporan Keuangan: Studi empiris pada Perusahaan Subsektor Apparel & Luxury Goods yang Terdaftar pada Bursa Efek Indonesia tahun 2020-2024 - Defri Thalia Audini; Melan Sinaga (Maslahah : Jurnal Manajemen dan Ekonomi Syariah, 2025)
This study aims to determine the effect of financial stability, external pressure, and auditor change on financial statement fraud in companies in the Apparel & Luxury Subsector, 2020-2024. The sample in this study was 14 companies in the Apparel & Luxury Subsector, covering the period 2020-2024. Data were obtained from company financial reports and then processed using Microsoft Excel 2018 and SPSS version 25. The research method used was multiple linear regression. The results of this study indicate that financial stability significantly influences financial statement fraud, external pressure significantly influences financial statement fraud, and auditor change significantly influences financial statement fraud.